STRATEGI CAPACITY BUILDING DALAM MENINGKATKAN KINERJA SDM PERENCANA DI BADAN KESATUAN BANGSA DAN POLITIK PROVINSI KALIMANTAN TENGAH - Jeri; Masrukin (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2025)
This study analyzes capacity-building strategies to enhance the performance of planning personnel at the Central Kalimantan Provincial Agency for National Unity and Political Affairs. For non-technical public organizations with limited resources, it remains unclear how capacity-building approaches can be adapted to support digital transformation demands. This qualitative case study was conducted over six months through in-depth interviews with seven informants, participatory observation, and document review. Data were analyzed using the Miles and Huberman interactive model. The findings reveal a gap between implemented strategies and organizational needs: current initiatives emphasize individual competency development through small-scale formal training and online learning with low participation, while organizational capacity elements such as knowledge management systems and structured collaborative learning forums remain underdeveloped. The study demonstrates that non-technical public organizations require low-cost, high-impact approaches grounded in internal collaborative learning to maximize limited human resource development investments.